Emergency evacuation in a supermarket during a terrorist attack: towards a possible modelling of the influence of affordances on the evacuation behavior of agents in a complex virtual environment - Satya Lancel; Vincent Chapurlat; Gérard Dray; Sophie Martin (Journal of Safety Science and Resilience, 2023)
During a terrorist attack on a supermarket, the use of emergency exits is essential for effective evacuation and saving lives. However, people tend to ignore emergency situations. This behavior can lengthen evacuation times, endanger individuals, and even prove fatal. In this context, we conducted a series of experiments to explore the links between cognition and the dynamics of human capabilities in a complex and changing environment. In a series of behavioral experiments and computer simulations, we found that active guidance by green flashing lights at emergency exits impacts the behavior of individuals in an emergency evacuation situation in a supermarket; this tested our hypothesis that changing the environment in turn changes the evacuation behavior of individuals. We also show that environmental modification can help in decision-making in an emergency situation. Furthermore, the results of computer simulations support a possible modeling of the influence of affordances on the evacuation behavior of agents in a complex virtual environment.